Peningkatan Kualitas Permukiman Dengan Pendekatan Disain Pada Bantaran Sungai di Kelurahan Kebonsari - Hapsari, Oktavi Elok; Prianto, Kusnul (EMARA Indonesian Journal of Architecture, 2016)
Housing and settlement are basic human needs and welfare in the merits of life. Other than serves as a residence, house has a strategic function in its role as the center of family education, cultural conformity and improving the future generations quality. Settlement as a life supported environment to do the activities and livelihood has a close connection with the setting of human behaviour varieties and social environment prevailing. Housing and residential development is not only based on phsyical development but should be linked to the social, economic and cultural life that supporting sustainable community. Settlement should provide the needs for its society that consists of five elements such as nature, man, society, shells, and network. Kebonsari Village which located on the south border of Malang became the object of this study. This is a qualitative descriptive research with participatory observational techniques. Kebonsari has a quite interesting topography because it is traversed by two streams, Mergan River and the Sukun River, flowing from north to south and located in the eastern region of Kebonsari. Existing problem that occurred in Kebonsari is related to the uncleanliness of Mergan river. In addition, supporting public facility in the settlement needs improvement, such as unkempt and barren footpath along the riverside, as well as the lack of communal space for the society. The result of this study is a concept design for the river-side area arrangement including footpath and communal space for the society in order to improving the quality of the settlement in Kebonsari.